Transformation of Islamic Criminal Law in Modern Society in Aceh - Efendi, Sumardi (Al-Qanun: Jurnal Kajian Sosial dan Hukum Islam, 2024)
This study examines the transformation of Islamic criminal law in modern Acehnese society, focusing on the implementation of the Qanun Jinayat, which governs the application of hudud, qisas, and ta'zir punishments. Aceh is the only province in Indonesia that officially enforces Sharia law, offering a unique case study to understand how Islamic criminal law is adapted in a modern context. This research employs a literature review method, gathering and analyzing various sources, including literature, journals, and legal documents related to the implementation of Islamic criminal law in Aceh. The findings indicate that while the enforcement of Islamic criminal law in Aceh enjoys significant support from the local population as part of their cultural and religious identity, substantial challenges remain, particularly regarding its alignment with human rights principles and national law. The study concludes that the transformation of Islamic criminal law in Aceh reflects efforts to balance the preservation of Islamic traditions with the demands of modernity. Nonetheless, continuous dialogue among stakeholders is necessary to ensure that the implementation of Sharia law in Aceh remains consistent with universal principles of justice and human rights.